Innovative startup: experience from Australia - Anh, Duong Hong; Thuy, Hoang Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
The paper deals with a study of actual status of start-up eco-system in Australia and support programs for start-up ecosystem offered by the Australian Government (CSIRO Innovation Funds, Businessmen Program, and Export Market Development Support Fund). The paper presents a look to forms of mobilization of capitals (possibilities to mobilize capitals from communities), forms of investment (start-up acceleration courses, start-up incubators, angel investors and venture investors) and reforms of legal policies (tax incentives, policy of protection of enterprises in case of bankruptcy) provided by the Australian Government to support enterprises to do innovative start-ups. Then the paper proposes lessons of experience for Vietnam in its efforts to build up a start-up nation. Code: 17110901